China’s international communications strategy in the context of the Belt and Road Initiative - Sun Xiaohan (Journal of the Belarusian State University. Journalism, 2021)
The article examines the problem of increasing the effectiveness of Chinese media in international media communication. The growth in the competitiveness of the Chinese media in the global media market is still insufficient in comparison with the country’s political and economic power. The aim of the study is to provide recommendations for improving external communication in the context of the Belt and Road Initiative, to find out what innovations in editorial policy and media management can contribute to this.